Relational studies between water intake and water distribution using GIS at mukim Siong, Baling, Kedah / Muhammad Azreen Abdul Halim - Abdul Halim, Muhammad Azreen (2020)
Since 2014 the people from Baling, Kedah having the water problem after the construction of the highway project has complete from Weng to Durian Burung. The villagers said there are many leaking pipelines but are not repaired more than three years ago by Syarikat Air Darul Aman (SADA) In this research, is discussed about the relational studies between water intake and water distribution at Mukim Siong, Baling Kedah. So, this study is to analysed the relational of water intake and water distribution in Mukim Siong. For this study are followed the several objectives which is to show the water distribution and water intake, second to identify the pattern of the factor that affected the water distribution and lastly to identify the relationship between water intake and water distribution. First process that been used is geocoding process using ArcGIS software to achieved the first objective. Spatial autocorrelation (Global Moran’s I) are used to show the pattern of the factor that affected the water distribution. Lastly to make the relationship depends the factor by using the Regression analysis using excel. The expected outcomes for this study to identify relationship of the factor that contribute water problems. This study hoped can help residents in the area overcome the problem of water distribution.